Policies for the elderly at social assistance facilities in the context of population aging in Vietnam - Nguyen Thi Thu Hoai (Journal of State Management, 2024)
Abstract: Population aging is a global issue, and Vietnam is one of the countries experiencing a rapid aging rate. Increased life expectancy reflects socio-economic and healthcare development advancements, indicating better care for individuals. However, it also poses challenges to the country's social welfare. In this context, the Government has issued social policies to support the elderly. This article describes the current state of population aging in Vietnam, highlights some issues, and proposes recommendations for social policies aimed at the elderly in social assistance facilities.